Filial piety and older adult caregiving among Chinese and Chinese-American families in the United States: a concept analysis - Chunhong Xiao; Patricia A. Patrician; Aoyjai P. Montgomery; Youhua Wang; Rita Jablonski; Adelais Markaki (BMC, 2024)
Abstract Background The culturally sensitive nursing practice has not embedded filial piety as a cultural value and stance pertaining to caregiving among aging Chinese and Chinese-American (CCA) families in the United States, yet it is critical for healthy aging among CCAs. Purpose To understand filial piety when caring for aging CCAs and conceptualize an operational definition and framework. Methods A systematic search was conducted in CINAHL, PubMed, Scopus, and PsycINFO databases. Analysis of the concept of filial piety among CCAs used Walker and Avant's methods. Twenty-six studies were selected in the final full-text analysis. Findings Synthesis of evidence identified four antecedents: (a) filial obligation as a 'cultural gene', (b) sense of altruism, (c) familial solidarity, and (d) societal expectation of 'birth right'. Attributes included familial material and emotional support, obedience, pious reverence, and societal norms. Consequences were related to caregiver burden, psychological and physical well-being, quality of life, and health equity. Conclusion Filial piety is an intrinsic desire to support aging parents and an extrinsic desire to adhere to Chinese societal moral tenets. The proposed operational framework "Caregiving for aging CCAs in the United States" merits further study.